2010
DOI: 10.1159/000316867
|View full text |Cite
|
Sign up to set email alerts
|

Individual Behavioral and Neuronal Phenotypes for Arginine Vasotocin Mediated Courtship and Aggression in a Territorial Teleost

Abstract: The neuropeptide arginine vasotocin (AVT) is well known to modulate both aggression and affiliation, yet few studies relate individual behavioral state to a quantitative assessment of AVT distribution in the brain. Here, using a wild population of beaugregory damselfish, Stegastes leucostictus, we assess: (1) the effect of AVT on courtship, and (2) with reference to our previous study on AVT modulation of aggression in this species, the relationship between AVT-like immunoreactive (ir) fiber distribution in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 138 publications
0
26
0
Order By: Relevance
“…Pupfish are behaviorally dimorphic, with males exhibiting higher levels of aggression and courtship than females [4]. The behavioral effects of AVT have likewise been found to be sexually dimorphic, usually with males -but not females -responding to exogenous AVT by altering aggressive or courtship behaviors [22,55,57] (see also [2,39,52,53,62]). Although, experiments remain to be conducted that would explicitly link the diurnal variation in v1a2 mRNA abundance in the brains of these wild pupfish to the daily shifts in aggressive and reproductive behaviors, rather than to the diurnal changes in water temperature, the sex-specific patterns of diurnal v1a2 mRNA regulation are consistent with the v1a2 receptor -but not the v1a1 receptor -mediating differential effects of AVT on behavior or neural physiology between males and females.…”
Section: Variation In V1a-type Receptor Mrna Abundance Among Sexual Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Pupfish are behaviorally dimorphic, with males exhibiting higher levels of aggression and courtship than females [4]. The behavioral effects of AVT have likewise been found to be sexually dimorphic, usually with males -but not females -responding to exogenous AVT by altering aggressive or courtship behaviors [22,55,57] (see also [2,39,52,53,62]). Although, experiments remain to be conducted that would explicitly link the diurnal variation in v1a2 mRNA abundance in the brains of these wild pupfish to the daily shifts in aggressive and reproductive behaviors, rather than to the diurnal changes in water temperature, the sex-specific patterns of diurnal v1a2 mRNA regulation are consistent with the v1a2 receptor -but not the v1a1 receptor -mediating differential effects of AVT on behavior or neural physiology between males and females.…”
Section: Variation In V1a-type Receptor Mrna Abundance Among Sexual Pmentioning
confidence: 99%
“…Studies of the endocrine basis for intraspecific variation have traditionally focused on gonadal steroids (e.g., androgens), as these hormones have well-established links to courtship, territorial aggression, and dominance behaviors. More recently, however, variation in sociosexual behaviors in vertebrates has also been linked to differences in arginine vasotocin/ vasopressin (AVT/AVP) and isotocin/mesotocin/oxytocin (IT/MT/ OT) signaling in the brain (e.g., [10,11,35,49,53], for reviews, see [3,5,21,23]). Whether manifest as differences in the neural circuits producing the peptides themselves, or as differences in the distribution, abundance and type of receptors -variation in nonapeptide hormone signaling within the brain appears a fundamental proximate mechanism underlying both inter-and intraspecific variation in sociosexual behaviors (e.g., [9,38,40,72], reviewed by [12,17,24,47]).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies in the roughskin newt (Taricha granulosa) demonstrated that injection with AVT increases male clasping behavior while infusions of AVP antagonists and anti-AVT serum reduce courtship (Moore and Zoeller, 1979;Moore and Miller, 1983). Courtship display behaviors such as attending behavior in fish (Semsar et al, 2001;Salek et al, 2002;Santangelo and Bass, 2010) and aspects of calling in several species of frogs including frequency and acoustic characteristics (Marler et al, 1995;Burmeister et al, 2001;Kime et al, 2007) are also affected. In zebra finches, exogenous AVT failed to significantly increase directed song (Goodson and Adkins-Regan, 1999;; however, a positive correlation between AVT-immunoreactive (AVT-ir) cell number in the bed nucleus of the stria terminalis and the number of courtship displays Arginine vasotocin, steroid hormones and social behavior in the green anole lizard (Anolis carolinensis) Leslie A. Dunham* and Walter Wilczynski performed was observed (Goodson et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their widespread distribution in the brain in mammals correlates with important roles as neuropeptides influencing social behavior [11,20] including social olfactory memory in mice [12] and trust and generosity in humans [28,53]. In fish the two peptides have been found to influence aggressive behavior [4,40,49]. During the past few years, genetic variants of the peptide receptors have been found to correlate with variation in different aspects of human social interaction, see for instance [51].…”
Section: Introductionmentioning
confidence: 99%